2013
DOI: 10.1002/jmv.23827
|View full text |Cite
|
Sign up to set email alerts
|

Serological cross reactivity to CMV and EBV causes problems in the diagnosis of acute hepatitis E virus infection

Abstract: Hepatitis E virus (HEV) infection is an important public health concern as a major cause of enterically-transmitted hepatitis worldwide. The detectable window of viraemia is narrow, and HEV IgM and IgG rise simultaneously in acute infection. Furthermore, previous investigators have shown HEV IgM false positive reactions occur against EBV, CMV and potentially hepatitis A. A retrospective analysis of HEV serology testing was performed at a London tertiary referral hospital over a 3-year period. A thousand four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 31 publications
(56 reference statements)
4
50
1
7
Order By: Relevance
“…In the first situation, multiple tests are performed for the same clinical syndrome and multiple positive results are generated, e.g., mononucleosis and CMV, EBV, and HIV infections (16)(17)(18)(19); acute hepatitis and HAV, HEV, CMV, and EBV infections (16,23,33); rash illness and measles virus, parvovirus, rubella virus, and HHV-6 infections (26,28,34,35); arbovirus CNS disease and WNV, St. Louis encephalitis (SLE) virus, and Jamestown Canyon virus infections (32,36); and arbovirus rash illness and Zika, dengue, and chikungunya virus infections (37,38). In the second situation, another etiology is confirmed by another method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first situation, multiple tests are performed for the same clinical syndrome and multiple positive results are generated, e.g., mononucleosis and CMV, EBV, and HIV infections (16)(17)(18)(19); acute hepatitis and HAV, HEV, CMV, and EBV infections (16,23,33); rash illness and measles virus, parvovirus, rubella virus, and HHV-6 infections (26,28,34,35); arbovirus CNS disease and WNV, St. Louis encephalitis (SLE) virus, and Jamestown Canyon virus infections (32,36); and arbovirus rash illness and Zika, dengue, and chikungunya virus infections (37,38). In the second situation, another etiology is confirmed by another method.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the test results may be inconclusive and may be reported as representative of a recent flavivirus infection (http://www.cdc.gov /zika/hc-providers/diagnostic.html). Herpesviruses are commonly associated with increases in heterologous IgM levels, crossreactivity, or subclinical reactivations leading to multiple positive IgM test results (16,17). Lyme disease IgM immunoblotting is prone to false positives because of inappropriate ordering, weak criteria for positivity, and inaccurate reading (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators hypothesized that alternative infectious agents may cause cross-reactivity of HEV EIAs, resulting in false positives. Other research has demonstrated EIA cross reactivity between EBV and CMV [1314], hepatitis A [15], and HIV [1617], suggesting a ‘molecular mimicry’ phenomenon. Our findings of a significant association between HIV and HEV IgM positivity, lack of HEV RNA, and lower rates of HEV EIA positivity among healthy control residents may be suggestive of such a process.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's initial Monospot test was negative which reflects the high false negative rate reported during the first week of symptoms [23]. Subsequent EBV and CMV IgM antibodies were both positive, likely due to high levels of cross-reactivity [24]. EBV PCR finally confirmed the diagnosis of primary EBV infection.…”
Section: Discussionmentioning
confidence: 79%